WAREHOUSE MANAGEMENT SYSTEM BERBASIS RADIO FREQUENCY IDENTIFICATION - Moh Muthohir; Rakasiwi, Sindhu; Ubaidillah , Lutfi (Jurnal Teknik Informatika dan Teknologi Informasi, 2023)
Minimarket Alfamart Kebondalem Kendal is one of the branch outlets of PT. Sumber Alfaria Trijaya Semarang where the management of the warehouse still uses conventional methods. Conventional management often creates difficulties in terms of the process of entering and leaving goods, knowing stock information, knowing the mutation of goods, and during the stock taking process. As a result of the difficulty in managing the warehouse, management cannot obtain warehouse information quickly and accurately. This makes warehouse productivity decrease because many items are not managed properly and disrupt operations. Based on the problems above, a prototype has been created that can help warehouse management by utilizing web-based RFID. The prototype system being developed will display goods data such as accurate stock, expiration date information, and history in out of goods which will be displayed on the web, so that stock-related information can be known quickly and the condition of goods in and out can be monitored at any time in real time